SYNCHRONIZATION OF ESTRUS WITH GnRH AND PGF2alpha DURING EARLY POSTPARTUM IN MEHSANA BUFFALOE - AWASTHl, M K; KAVANI, F S; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
Present experiment was conducted to assess efficacy of estrus synchronization protocol usingcombination of GnRH and PGF2alpha  administration in postpartum Mehsana buffaloes (n=12) beginning onday 35 postpartum (day O for proposed protocol) with 20 μg Buserelin acetate i/m, followed by i/minjection of 25 mg Dinoprost tromethamin 10 days later. Another 6 animals of similar reproductive statuswere kept as control. Estrus was detected in animals twice daily and estrus animals were served withknown fertile buffalo bull. Three animals showed premature estrus between days O and 10, i.e. prior toinjection of prostaglandin, while 4 animals (33.33%) exhibited synchconized estrus after PGF2alpha  treatment.One animal with premature estrus and three animals with synchronized estrus conceived after serviceat induced estrus giving overall conception rate of 57.14% (4,7), whereas overall pregnancy rate was33.33% (4/12). When the subsequent reproductive performance was compared between animals oftreatment and control groups non-significant difference was recorded in occurrence of first postpartumestrus (74.5 ± 10.24 vs. 59.33 ± 7.92 days), calving to conception interval (95.0 ± 12.10vs. 77.0 ± 20.36days) and number of services per conception ( 1.50 ± 0.24 vs. 1.50 ± 0.37). From the present study, it isconcluded that estrus synchronization protocol using combination of GnRH and PGF2alpha  administrationmay induce fertile estrus, however, there was no beneficial effect on subsequent reproductive performanceof treated animals.
Keywords: Water buffaloes; postpartum; Estrus synchronization; Reproductive performance